2010
DOI: 10.1073/pnas.0913562107
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis dynamin-related proteins DRP2B and DRP1A participate together in clathrin-coated vesicle formation during endocytosis

Abstract: Endocytosis performs a wide range of functions in animals and plants. Clathrin-coated vesicle (CCV) formation is an initial step of endocytosis, and in animal cells is largely achieved by dynamins. However, little is known of its molecular mechanisms in plant cells. To identify dynamin-related proteins (DRPs) involved in endocytic CCV formation in plant cells, we compared the behaviors of two structurally different Arabidopsis DRPs, DRP2B and DRP1A, with those of the clathrin light chain (CLC), a marker of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
168
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(186 citation statements)
references
References 37 publications
(4 reference statements)
17
168
0
Order By: Relevance
“…The size of these early endosomes (approximately 1 mm) suggest that they may be clathrin-coated vesicles. 22,31 The absence of Sytox Green fluorescence in the nucleus of these cells confirmed that they were alive, so that the internalization of the FM dye cannot be attributed to cell death. In fact, cells pretreated with DMSO 10% died and serve as a positive control for Sytox Green stain (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The size of these early endosomes (approximately 1 mm) suggest that they may be clathrin-coated vesicles. 22,31 The absence of Sytox Green fluorescence in the nucleus of these cells confirmed that they were alive, so that the internalization of the FM dye cannot be attributed to cell death. In fact, cells pretreated with DMSO 10% died and serve as a positive control for Sytox Green stain (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The aggregation of PIN2:GFP at certain sites of the PM is similar to the behavior of DRP1A and 1C under the Tyrphostin A23 treatment. Dynamics of these proteins was disturbed and the size of the foci at the PM to which fluorescent protein-tagged DRP1s localize was increased (Konopka et al, 2008;Fujimoto et al, 2010). Moreover, the localization pattern of PIN2:GFP in the ap2m-1 mutant filaments was phenocopied by treatment of the wild type with Tyrphostin A23.…”
Section: Ap2m Plays a Crucial Role In Modulating Cellular Auxin Levelmentioning
confidence: 90%
“…4c,d), indicating that continuous vesicle trafficking is required for creating CHER1 polarization in SE. Furthermore, we analysed the behaviour of two dynamin-related proteins, DRP1A and DRP1C, which are involved in the clathrinmediated endocytosis in plants [42][43][44] . As previously reported, both DRP1A and DRP1C localize to the cell plate and the plasma membrane of expanding and fully expanded interphase cells 44,45 .…”
Section: Resultsmentioning
confidence: 99%